Investigation Of The Perceived Mobbing Behaviours By Counselor Teachers - Murside EMIROGLU (Muhammed Yıldız, 2017)
The aim of this study is to research into the mobbing behaviour perceived by teacher counsellors in terms of variables. Descriptive research method has been used in this study. The universe of this study has included the teacher counsellors working at Gaziantep. As it is desired to be reached the whole of the universe in the study, the way of sampling is not preferred. 219 teachers working on seven different districts of Gaziantep have comprised the sample group of this study. With the purpose of providing the description of the personal information of the people included in the study, ‘Occupational Satisfaction Scale’ has been used, and with the purpose of evaluating the perceived mobbing behaviour ‘Mobbing Detection Scale’ which includes 35 items has been used. Data collection tools were delivered to the schools with a directive and they were retaken in closed envelopes. The obtained data was analyzed with SPSS program. With the aim of determining whether occupational satisfaction and personal variables predicts the perceived mobbing, regression analysis has been used in the study. The variables of marital status, educational level, occupational seniority and school types have been found to be a meaningful predictor of mobbing behaviour perceived by teacher counsellors. Suggestions have been developed in line with the obtained data. Key